I need help with this problem.

Let two real-valued functions $f,g$ be equal to the $n'$th order at $a$ if

$$\lim_{h\rightarrow 0}\frac{f(a+h)-g(a+h)}{h^n} = 0 $$

If $f'(a),\ldots,f^n(a)$ exist, show that $f$ and the function $g$ be given by

$$g(x) = \sum_{i=0}^n \frac{f^{(i)}(a)}{i!}(x-a)^i$$

are equal up to the $n$'th order at $a$.

I'm also given the following hint. The limit

$$\lim_{x\rightarrow a}\frac{f(x) -\sum_{i=0}^{n-1}\frac{f^{(i)}(a)}{i!}(x-a)^i}{(x-a)^n} $$

may be evaluated using L'Hospital's rule.

Can't I just plug in $g(a+h)$ and apply L'Hopital $n$ times? I'm not sure what to do with this hint.


If you plug $x-a$ into $h$ in the definition of $n$th order, you end up evaluating that limit. You can then apply L'Hopital's Rule enough times to evaluate the limit.


The sum only goes up to $n-1$. That's because you can separate out the $n$th term to get

$$ -\frac{\frac{f^{(n)}(a)}{n!}(x-a)^n}{(x-a)^n}=-\frac{f^{(n)}(a)}{n!} $$

for $x\neq a$.

  • $\begingroup$ I want to know how I'm supposed to use the hint I'm given. $\endgroup$ – Fred May 25 '12 at 1:19
  • $\begingroup$ @Fred My answer says that you can evaluate the limit that proves they are $n$th order by substituting in $x-a$ for $h$. Then you will have the limit in the hint. The hint says to use L'Hopitals to evaluate this new limit that is equal to the old limit. $\endgroup$ – Joe Johnson 126 May 25 '12 at 1:21
  • $\begingroup$ The sum goes up to $n-1$ though and not $n$. That's where I'm confused. $\endgroup$ – Fred May 25 '12 at 1:26
  • $\begingroup$ @Fred I added to my solution. $\endgroup$ – Joe Johnson 126 May 25 '12 at 1:46

The definition you are given is equivalent to

$$\lim_{x \to a} \frac{f(x)-g(x)}{(x-a)^n}=0 $$

We are given $g$ defined as the sum

$$g(x) = \sum_{i=0}^n \frac{f^{(i)}(a)}{i!}(x-a)^i$$

so we want to check wether or not

$$\lim_{x \to a} \frac{f(x)-\sum_{i=0}^n \frac{f^{(i)}(a)}{i!}(x-a)^i}{(x-a)^n}=0 $$

Since the last term has $(x-a)^n$ in it, we can take it out and get

$$\lim_{x \to a} \frac{f(x)-\sum_{i=0}^{n-1} \frac{f^{(i)}(a)}{i!}(x-a)^i}{(x-a)^n}-\frac{f^{(n)}(a)}{n!}= $$

The sum is a polynomial in $(x-a)$ of degree $n-1$, which, as well as $f$, has its $k^{th}$ derivative defined for $k=0,1,\dots,n$, so we can use L'Hôpital Bernoulli to find the indeterminate limit. Applying it $n-1$ times gives

$$\frac 1 {n!}\mathop {\lim }\limits_{x \to a} \frac{{{f^{\left( {n - 1} \right)}}(x) - {f^{\left( {n - 1} \right)}}\left( a \right)}}{{\left( {x - a} \right)}} - \frac{{{f^{(n)}}(a)}}{{n!}} = $$

And by definition of the derivative you get

$$\frac{{{f^{(n)}}(a)}}{{n!}} - \frac{{{f^{(n)}}(a)}}{{n!}} = 0$$

Note we can apply L'Hôpital in every $n-1$ step because it is the case in every step we face a $\frac 0 0 $ indeterminate form.

What you are asked to prove is usually stated as

$$f(x) = T_n^a(x)+o((x-a)^n)\text{ ; when } x \to a$$

and means the error is of greater order (it goes to zero faster) than $(x-a)^n$ when $x \to a$. Though confusing, the meaning of "greater order" might be cleared up with this example: $(x-a)^{n+1}$ is of greater order than $(x-a)^n$, and thus goes to $0$ "faster" than it for $x \to a$, since

$$\mathop {\lim }\limits_{x \to a} \frac{{{{\left( {x - a} \right)}^{n + 1}}}}{{{{\left( {x - a} \right)}^n}}} = \mathop {\lim }\limits_{x \to a} \left( {x - a} \right) = 0$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.